Research on Blockchain Consensus Algorithm based on DWBA Protocol - Fang, Jialing (2022 IEEE International Conference on Artificial Intelligence and Computer Applications (ICAICA), 2022)
In the development process of the information industry, the identification technology of digital products is widely used. In this process, it is particularly critical to pay attention to the blockchain information of digital products of the information industry. The information security of digital products of the information industry has also become one of the new generations of people's livelihood development issues. To solve the above problems, it is necessary to continuously develop by expanding the blockchain protocol system of digital products of the information industry. This paper mainly uses the combination of the current blockchain technology and the expansion technology of the blockchain protocol of the digital products of the information industry, through the definition and distribution of the smart contract and based on the blockchain technology, to design a blockchain protocol for the digital products of the smart contract information industry and expansion system. This paper first analyzes blockchain technology's formation and technical core in detail. And it proposes an effective combination of blockchain protocol extension and blockchain for digital products in the information industry and designs related systems.